2009
DOI: 10.1128/aem.01426-08
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Inactivation of Spores of ProteolyticClostridium botulinumStrains by High Pressure and Heat Is Strain and Product Dependent

Abstract: The combined high pressure and heat resistances of spores of five proteolytic Clostridium botulinum strains and of the nonpathogenic surrogate strain Clostridium sporogenes PA3679 were compared with their heat-only resistances on the basis of equivalent accumulated thermal lethality, expressed as equivalent minutes at a reference temperature of 105°C (F 105°C ). Comparisons were made with three model (i.e., diluted) products, namely, 30% (wt/wt) Bolognese sauce, 50% (wt/wt) cream sauce, and rice water agar. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 33 publications
2
54
0
Order By: Relevance
“…The Bolognese sauce, cream sauce, and rice were diluted to 30, 50, and 40% (wt/wt), respectively, with SDW and blended as described previously (7). The water from the blended rice mixture was combined 1:1 with 3% (wt/vol) molten agar as previously described (7). The addition of agar was required to provide greater control of the prepressurization heating process.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Bolognese sauce, cream sauce, and rice were diluted to 30, 50, and 40% (wt/wt), respectively, with SDW and blended as described previously (7). The water from the blended rice mixture was combined 1:1 with 3% (wt/vol) molten agar as previously described (7). The addition of agar was required to provide greater control of the prepressurization heating process.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we have shown that, in laboratory scale experiments, the inactivation of spores of proteolytic Clostridium botulinum by HPT processing is similar to that achieved under thermal-only processing conditions compared on the basis of accumulated thermal lethality (F T z ) (7). While we have noted some synergy between heat and high pressure for the inactivation of spores of proteolytic C. botulinum, this synergy appears to be dependent on both the strain and the product (7). Contrary to the case for proteolytic C. botulinum, there are a number of published studies suggesting that the most heat-resistant spoilage bacterium of concern for LASSF, Geobacillus stearothermophilus, is not nearly as resistant to thermal processing under high pressure as its heat resistance would predict (2,14,17,21,24).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, a study by Bull et al (49) examined the resistance of NCTC8594 spores to combined high temperature and pressure in various food matrices and compared it with that of spores of C. botulinum strains 7273B, 62-A, 213B, and NCTC2916 under the same conditions. They found that NCTC8594 was more sensitive to combined high temperature and pressure than the majority of C. botulinum spores tested and concluded that NCTC8594 may not be a suitable surrogate for C. botulinum, at least for high-pressure thermal process validation studies (49).…”
Section: Discussionmentioning
confidence: 99%
“…Non-heat-treated controls were heat shocked at 80°C for 10 min and are reported as spore-forming units per milliliter. to batch as well as being strain dependent (9,26,49,57,58). Based on the results of this study, a reexamination and reevaluation of the thermal destruction data reported in the literature based on the "isolate" of PA 3679 used in a particular study are warranted.…”
Section: Discussionmentioning
confidence: 99%